Interactions Between Lower- and Higher-Level Processing When Reading in a Second Language: An Eye-Tracking Study. - Hessel, Annina K.; Schroeder, Sascha (Discourse Processes, 2020)
This experiment investigated interactions between lower- and higher-level processing when reading in a second language (L2). We conducted an eye-tracking experiment with the within-subject manipulation inconsistency (to tap higher-level coherence-building) crossed with a within-subject manipulation of word-processing difficulty (to alter the ease of lower-level processing), both manipulated on the text level. Sixty-three L2 learners read 48 short expository texts containing inconsistencies created through mismatches between pretargets such as soya and targets such as corn, or consistent controls. Word-processing difficulty was manipulated by inserting either shorter and higher-frequency words such as often or longer and lower-frequency words such as increasingly. We found evidence of interactions between lower-level word-processing difficulty and higher-level coherence building, as revealed by reduced a inconsistency effect showing in go-past durations and rereading in the difficult condition. This effect did not, however, extend to targeted regressions into inconsistent information. Our findings provide the first experimental evidence for online interactions between lower-level word processing and higher-level coherence building.